Characterization of immune checkpoint inhibitor‐induced cardiotoxicity reveals interleukin‐17A as a driver of cardiac dysfunction after anti‐PD‐1 treatment. (13th December 2022) - Gergely, Tamás G.; Kucsera, Dániel; Tóth, Viktória E.; Kovács, Tamás; Sayour, Nabil V.; Drobni, Zsófia D.; Ruppert, Mihály; Petrovich, Balázs; Ágg, Bence; Onódi, Zsófia; Fekete, Nóra; Pállinger, Éva; et al.
Abstract : Background and Purpose: Immune checkpoint inhibitors (ICI), such as anti‐PD‐1 monoclonal antibodies, have revolutionized cancer therapy by enhancing the cytotoxic effects of T‐cells against tumours. However, enhanced T‐cell activity also may cause myocarditis and cardiotoxicity. Our understanding of the mechanisms of ICI‐induced cardiotoxicity is limited. Here, we aimed to investigate the effect of PD‐1 inhibition on cardiac function and explore the molecular mechanisms of ICI‐induced cardiotoxicity. Experimental Approach: C57BL6/J and BALB/c mice were treated with isotype control or anti‐PD‐1 antibody. Echocardiography was used to assess cardiac function. Cardiac transcriptomic changes were investigated by bulk RNA sequencing. Inflammatory changes were assessed by qRT‐PCR and immunohistochemistry in heart, thymus, and spleen of the animals. In follow‐up experiments, anti‐CD4 and anti‐IL‐17A antibodies were used along with PD‐1 blockade in C57BL/6J mice. Key Results: Anti‐PD‐1 treatment led to cardiac dysfunction and left ventricular dilation in C57BL/6J mice, with increased nitrosative stress. Only mild inflammation was observed in the heart. However, PD‐1 inhibition resulted in enhanced thymic inflammatory signalling, where Il17a increased most prominently. In BALB/c mice, cardiac dysfunction was not evident, and thymic inflammatory activation was more balanced. Inhibition of IL‐17A prevented anti‐PD‐1‐induced cardiac dysfunction in C57BL6/J mice. Comparing myocardial transcriptomic changes in C57BL/6J and BALB/c mice, differentially regulated genes ( Dmd, Ass1, Chrm2, Nfkbia, Stat3, Gsk3b, Cxcl9, Fxyd2, and Ldb3 ) were revealed, related to cardiac structure, signalling, and inflammation. Conclusions: PD‐1 blockade induces cardiac dysfunction in mice with increased IL‐17 signalling in the thymus. Pharmacological inhibition of IL‐17A treatment prevents ICI‐induced cardiac dysfunction. Abstract :